Model‐Based Product Line Engineering to Plan and Track Submarine Configuration. Issue 2 (21st August 2019) - Hause, Matthew; Hallett, Jon
ABSTRACT: One can measure the life of a class of submarines in decades. As such, the operational demands and expectations change both strategically and tactically over its lifetime. Coupling this adaptability with the length of time submarines take to design, build, and maintain, no two as‐built submarines in a class will ever be the same, even when constructed/maintained to the same build‐to design. Traditionally, we have accepted this as the standard, and in most cases the configuration management team managed the full information set at a class or batch level, but not at an individual submarine level. The team managed the configuration of an individual submarine in terms of agreed changes against the class or batch baseline. Advances in technology (hardware performance, software tools, and standards) now give us the opportunity to not only manage the full information set related to individual submarine system configuration baselines as they change over time, but also undertake rigorous model‐based trade‐off studies to plan the manner in which we can modify a class, a batch, an individual submarine (variant), or any combination thereof over time. This paper will explore the use of model‐based systems engineering (MBSE) coupled with recent developments of product line engineering (PLE)/orthogonal variability modelling (OVM) to provide a means to plan, track, manage, and evaluate an individual submarine's configuration over time in the context of the class, whilst simultaneously highlighting the wider application in the submarine enterprise and beyond.